Profiling language learners in hybrid learning contexts: Learners’ perceptions - Pekka Lintunen (The EUROCALL Review, 2017)
This article discusses formal and informal foreign language learning before university level. The focus is on beginning university students’ perceptions of their earlier learning experiences, especially in digital contexts. Language learners’ digital competence is a part of their everyday lives, but its relationship to learning in and outside educational settings is still relatively seldom studied. The article discusses learning in formal and informal (i.e., hybrid) contexts and digital learning profiles −that is, a learner’s own personalized style in acquiring language competence by creating affordances in personalized digital or mobile learning environments− in primary and secondary education identified in a language learning survey. The results are based on an online survey sent to all beginning university students majoring in languages at a Finnish university (N= 87/192), which was complemented by a short narrative task (N=47) a few months later focusing on earlier education and the use of language learning technologies. The results suggest that the use of technologies seems to differ between extramural and in-school language learning. The learners were well aware of various possibilities to create affordances for learning, and their own involvement increased with age. Most participants had positive attitudes towards the use of technologies to enhance language learning, but critical views emphasized the importance of inspiring contact teaching. Three different digital learning profiles were identified: a digiage learner, a hybrid learner, and an in-school learner. These can be useful when planning differentiated foreign language instruction.